Mechanisms of vapor‐phase antibacterial action of essential oil from Cinnamomum camphora var. linaloofera Fujita against Escherichia coli. Issue 8 (4th July 2019) - Wu, Kegang; Lin, Yahui; Chai, Xianghua; Duan, Xuejuan; Zhao, Xinxin; Chun, Chen
Abstract: The purpose of this study was to investigate antibacterial activity of essential oil from Cinnamomum camphora var. linaloofera Fujita (EOL) at vapor phase and its mechanism of bactericidal action against Escherichia coli . Results showed that the vapor‐phase EOL had significant antibacterial activity with a minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of 200 μl/L. Further analyses showed that treatment of E. coli with vapor‐phase EOL resulted in partial degradation of cell membrane, increased membrane permeability, leakage of cytoplasm materials, and prominent distortion and shrinkage of bacterial cells. FTIR showed that EOL altered bacterial protein secondary and tertiary structures. GC/MS analysis showed that the components of vapor‐phase EOL included linalool (69.94%), camphor (10.90%), nerolidol (10.92%), and safrole (8.24%), of which linalool had bactericidal activity. Quantum chemical analysis suggested that the antibacterial reactive center of linalool was oxygen atom (O10 ) which transferred electrons during antibacterial action by the donation of electrons. Abstract : The antibacterial reactive center of linalool was oxygen atom (O10) which transfered electrons during antibacterial action by the donation of electrons.